Pengaruh Motivasi Kerja, Kompetensi dan Kompensasi Terhadap Kinerja Agen Asuransi di Kantor Pemasaran Mandiri Cakra Ning Nusa PT. Sun Life Denpasar - Swandayani, Rahayu; Wimba, I Gusti Ayu; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of work motivation, competence and compensation on the performance of insurance agents at the Mandiri Cakra Ning Nusa Marketing Office of PT Sun Life Denpasar. The population is all 97 insurance agents at the Mandiri Cakra Ning Nusa Marketing Office of PT Sun Life Denpasar, so the census method is used. The method of data collection uses questionnaires, observations, interviews and documentation studies. The data analysis techniques used are Multiple Linear Regression Analysis, determination coefficient analysis, Significant test t and Significant test F. Results of this study are 1) T value calculate variable work motivation = 2.458, significant value is 0.016 < ? = 0.05 then work motivation has a positive and significant effect on the performance of insurance agents. 2) the T value calculates the competency variable = 2.997 and the significant value is 0.003 <? = 0.05 then the competence has a positive and significant effect on the performance of the insurance agent. 3) the value of T calculate the variable compensation = 2.701 and the significant value is 0.008 <? = 0.05 then the compensation has a positive and significant effect on the performance of the insurance agent (4) The value of F-count 119.386 is greater than the value of F-table 3.09 then work motivation, competence and compensation simultaneously have a positive and significant influence on the performance of the insurance agent. Advice for subsequent researchers to supervise the work of agents, provide training and training for insurance agents to improve their work ability.